Peningkatan Motivasi Belajar Peserta Didik Dalam Mata Pelajaran Akidah Akhlak Dengan Menggunakan Asesmen Formatif Studi Pada Fase D - Salamudin, Ceceng; Kusnadi, Rindiani (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
This study discusses the improvement of students' learning motivation in Akidah Akhlak learning using formative assessment. The low level of learning motivation is the main reason this research was conducted. The observation results show that only about 21% of 33 students are classified as good in learning. Therefore, an interesting evaluation stimulus or learning assessment test is needed, one of which is by using formative assessment. The purpose of this study was to describe the use of formative assessment in increasing the learning motivation of students in learning Akidah akhlak phase D at MTs Al-Musaddadiyah Garut. The research method used is Classroom Action Research (CAR) with two cycles. Data collection techniques include observation, questionnaires, interviews, and documentation. The data analysis technique used simple statistical analysis to calculate the average value and percentage of learning completeness. In cycle I, there was an increase of 52%, and in cycle II it increased again to 87%. Overall, the increase in learning motivation from pre-cycle to cycle II reached 66%.         Keywords: Learning Motivation, Formative Assessment, Akidah Akhlak Learning.